Emerging Roles of TRIM56 in Antiviral Innate Immunity - Wang, Dang; Li, Kui (Viruses, 2025)
The tripartite-motif protein 56 (TRIM56) is a RING-type E3 ubiquitin ligase whose functions were recently beginning to be unveiled. While the physiological role(s) of TRIM56 remains unclear, emerging evidence suggests this protein participates in host innate defense mechanisms that guard against viral infections. Interestingly, TRIM56 has been shown to pose a barrier to viruses of distinct families by utilizing its different domains. Apart from exerting direct, restrictive effects on viral propagation, TRIM56 is implicated in regulating innate immune signaling pathways that orchestrate type I interferon response or autophagy, through which it indirectly impacts viral fitness. Remarkably, depending on viral infection settings, TRIM56 either operates in a canonical, E3 ligase-dependent fashion or adopts an enzymatically independent, non-canonical mechanism to bolster innate immune signaling. Moreover, the recent revelation that TRIM56 is an RNA-binding protein sheds new light on its antiviral mechanisms against RNA viruses. This review summarizes recent advances in the emerging roles of TRIM56 in innate antiviral immunity. We focus on its direct virus-restricting effects and its influence on innate immune signaling through two critical pathways: the endolysosome-initiated, double-stranded RNA-sensing TLR3-TRIF pathway and the cytosolic DNA-sensing, cGAS-STING pathway. We discuss the underpinning mechanisms of action and the questions that remain. Further studies understanding the complexity of TRIM56 involvement in innate immunity will add to critical knowledge that could be leveraged for developing antiviral therapeutics.